2017
DOI: 10.1200/jco.2016.71.0228
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Progression-Free and Overall Survival in Patients With Unresectable or Metastatic GI Stromal Tumors: Long-Term Analysis of the European Organisation for Research and Treatment of Cancer, Italian Sarcoma Group, and Australasian Gastrointestinal Trials Group Intergroup Phase III Randomized Trial on Imatinib at Two Dose Levels

Abstract: Purpose To report on the long-term results of a randomized trial comparing a standard dose (400 mg/d) versus a higher dose (800 mg/d) of imatinib in patients with metastatic or locally advanced GI stromal tumors (GISTs). Patients and Methods Eligible patients with advanced CD117-positive GIST from 56 institutions in 13 countries were randomly assigned to receive either imatinib 400 mg or 800 mg daily. Patients on the 400-mg arm were allowed to cross over to 800 mg upon progression. Results Between February 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
155
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(166 citation statements)
references
References 18 publications
5
155
3
3
Order By: Relevance
“…Subsequently, several clinical trials demonstrated the efficacy of targeting the mutant KIT oncoprotein in patients with metastatic GIST with the tyrosine kinase inhibitor (TKI) imatinib mesylate (Gleevec, Novartis, Basel, Switzerland) 5 10 . Patients treated with imatinib experienced durable periods of disease control, with a median progression-free survival (PFS) of 2 years, and median overall survival (OS) of 5 years, compared to historical median OS of 9 months 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, several clinical trials demonstrated the efficacy of targeting the mutant KIT oncoprotein in patients with metastatic GIST with the tyrosine kinase inhibitor (TKI) imatinib mesylate (Gleevec, Novartis, Basel, Switzerland) 5 10 . Patients treated with imatinib experienced durable periods of disease control, with a median progression-free survival (PFS) of 2 years, and median overall survival (OS) of 5 years, compared to historical median OS of 9 months 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 80% of GIST tumors have a gain-of-function mutation of the c-kit or PDGF receptor [6,7,8]. Targeted therapy with the small-molecule RTKI imatinib has led to a dramatic improvement of the prognosis of patients with metastatic GIST [9,10,11]. The European Medicines Agency and the Food and Drug Administration did not only approve imatinib for the treatment of metastatic disease but also as an adjuvant therapy for patients with a significant risk of tumor recurrence [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The biological basis is unknown, but, given the similar profile of KIT exon 11 mutations across both groups, it is possible that some steps of the typical cytogenetic progression from microGIST to metastatic GIST are missed during tumor evolution in LTRs . Nonetheless, more studies are warranted to identify molecular biomarkers for LTR at baseline, as few prognostic factors at baseline have emerged from this and prior studies . This is nontrivial, because a priori stratification of patients with GIST according to response could modify management and follow‐up, given the striking differences in PFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…In the B2222 study, approximately 30% of the patients remained progression‐free after 5 years on continuous imatinib treatment . Recent updates from the two phase III trials reported a 10‐year PFS estimate of 7%–9%, therefore highlighting that a subgroup of patients with metastatic GIST are exquisitely sensitive to KIT/PDGFRA signaling inhibition with imatinib .…”
Section: Introductionmentioning
confidence: 99%